Biosynthesis of a galactose- and galacturonic acid-containing polysaccharide in Rhizobium meliloti - Ugalde, R.A. (1986)
Previous work showed that two different strains derived from a culture of Rhizobium meliloti 102F51 differed with respect to phage specificity, agglutinability by alfalfa seed lectin, and synthesis of a galactose-containing polysaccharide (R.A. Ugalde, J. Handelsman, and W.J. Brill, J. Bacteriol. 166:148-154, 1986). Inner membranes from the more competitive strain incorporated glactose from UDP-galactose when a thermostable factor was present. This factor has now been identified as UDP-galacturonic acid. UDP-glucuronic acid was also active as a donor; however, this activity may be due to the presence of a 4-epimerase. Galacturonic acid, together with galactose, is incorporated into the reaction product, which appears to be a polysaccharide formed by several repeating units of these two monosaccharides. Partial acid hydrolysis liberates the disaccharide with galactose at the reducing end.